2018
DOI: 10.1371/journal.pntd.0006748
|View full text |Cite
|
Sign up to set email alerts
|

Dengue seroprevalence in a cohort of schoolchildren and their siblings in Yucatan, Mexico (2015-2016)

Abstract: BackgroundThe implementation of vector control interventions and potential introduction new tools requires baseline data to evaluate their direct and indirect effects. The objective of the study is to present the seroprevalence of dengue infection in a cohort of children 0 to 15 years old followed during 2015 to 2016, the risk factors and the role of enhanced surveillance strategies in three urban sites (Merida, Ticul and Progreso) in Yucatan, Mexico.MethodsA cohort of school children and their family members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
6
12
0
Order By: Relevance
“…Manuscript to be reviewed Dengue cases were less likely to report living in a house or apartment (recorded as "other" in the study questionnaire). This was also observed in a seroprevalence study in Mexico where these patients reported a "shared" living arrangement (Pavia-Ruz et al 2018). Other aspects of the home environment evaluated in our study did not differ between dengue and non-dengue cases.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Manuscript to be reviewed Dengue cases were less likely to report living in a house or apartment (recorded as "other" in the study questionnaire). This was also observed in a seroprevalence study in Mexico where these patients reported a "shared" living arrangement (Pavia-Ruz et al 2018). Other aspects of the home environment evaluated in our study did not differ between dengue and non-dengue cases.…”
Section: Discussionsupporting
confidence: 86%
“…The absence of air conditioning and window screens did not appear to increase the risk for DENV infection. However, complete screening of the home and air conditioning have been associated with decreased vector indices and dengue incidence in other settings (Manrique-Saide et al 2015;Pavia-Ruz et al 2018;Reiter et al 2003;Waterman et al 1985), and the addition of screens has been proposed as a means of DENV control through improvements to the built environment (Lindsay et al 2017;Vazquez-Prokopec et al 2016). Our findings may indicate that patients acquired DENV outside the home or that the use of these interventions is incomplete (e.g.…”
Section: Discussionmentioning
confidence: 75%
“…The incidence of symptomatic dengue infections observed during the same period was 3.5 cases per 1000 person-years (95% CI 1.9, 5.9). The majority of seroconversions occurred in the younger age groups (≤ 14 years old) [37][38][39]. The incidence of symptomatic chikungunya illness was 8.6 per 1000 person-years (95% CI 5.8, 12.3) and the incidence rate of symptomatic Zika illness was 2.3 per 1000 person-years (95% CI 0.9, 4.5) [37].…”
Section: Study Areamentioning
confidence: 99%
“…ABV transmission in Merida is seasonal, beginning in July and peaking in October-November. Baseline serological information (captured by ELISA methods) on natural ABV infection rates has been collected from Merida in 2015-2016 through a school-based cohort that followed all family members living in the same household as the enrolled children [37][38][39]. In 2015, DENV seroprevalence in the cohort was 70.2%, which increased with age from 31% in 0-8-year-olds to 79% in adults ≥ 20 years.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation